Producing inclusive feminist knowledge : positionalities and discourses in the global south - Ampofo, Akosua Adomako; Beoku-Betts, Josephine (Advances in gender research., 2021)
In the global South there is growing concern about the dynamics of global politics that have the potential to marginalize the diverse voices and perspectives of subaltern communities. Exploring ongoing and new feminist dialogues in the global South, this book examines the ways in which dominant epistemologies are challenged, unique identities formed, and the implications for the global feminist agenda. With chapters addressing feminist issues in Africa, South Asia, the Middle East, Latin America, and the Caribbean, the authors explore how feminist scholars and activists consciously challenge dominant hegemonic discourses and methodologies. The volume raises several critical questions: How do Southern feminist scholars and activists conceptualize and interpret the multiple facets of women's lived experiences in their societies? What factors shape their positionality and identity as feminist scholars and activists? How do Southern feminist discourses offer possibilities of new insights that reflect the multiple and shifting conditions in their societies? What might their perspectives bring to global feminist agendas? This volume offers a space within which feminist voices from multiple locations in and on the global South can find expression in conversations that redefine, reconfigure, and envision knowledge production from their standpoints and in ways that positively impact the lives of women in the global South.